Select Page  1. Find the nth term formula for the following quadratic sequence: 22, 29, 40, 55, 74
2. Find the nth term formula for the following quadratic sequence: 22, 29, 40, 55, 74
3. Find the nth term formula for the following quadratic sequence: 5, 13, 25, 41, 61
4. Find the nth term formula for the following quadratic sequence: 19, 29, 45, 67, 95
5. Find the nth term formula for the following quadratic sequence: 15, 25, 41, 63, 91
6. Find the nth term formula for the following quadratic sequence: 13, 25, 43, 67, 97
7. Find the nth term formula for the following quadratic sequence: 7, 17, 33, 55, 83
8. Find the nth term formula for the following quadratic sequence: 20, 27, 38, 53, 72
9. Find the nth term formula for the following quadratic sequence: 5, 13, 25, 41, 61
10. Find the nth term formula for the following quadratic sequence: 17, 24, 35, 50, 69
11. Find the nth term formula for the following quadratic sequence: 13, 19, 27, 37, 49
12. Find the nth term formula for the following quadratic sequence: 13, 21, 33, 49, 69
13. Find the nth term formula for the following quadratic sequence: 8, 20, 38, 62, 92
14. Find the nth term formula for the following quadratic sequence: 9, 13, 19, 27, 37
15. Find the nth term formula for the following quadratic sequence: 4, 9, 16, 25, 36
16. Find the nth term formula for the following quadratic sequence: 17, 25, 37, 53, 73
17. Find the nth term formula for the following quadratic sequence: 14, 24, 40, 62, 90
18. Find the nth term formula for the following quadratic sequence: 18, 26, 38, 54, 74
19. Find the nth term formula for the following quadratic sequence: 9, 21, 39, 63, 93
20. Find the nth term formula for the following quadratic sequence: 9, 20, 37, 60, 89  1. nth = 2n² + n + 19
2. nth = 2n² + n + 19
3. nth = 2n² + 2n + 1
4. nth = 3n² + n + 15
5. nth = 3n² + n + 11
6. nth = 3n² + 3n + 7
7. nth = 3n² + n + 3
8. nth = 2n² + n + 17
9. nth = 2n² + 2n + 1
10. nth = 2n² + n + 14
11. nth = n² + 3n + 9
12. nth = 2n² + 2n + 9
13. nth = 3n² + 3n + 2
14. nth = n² + n + 7
15. nth = n² + 2n + 1
16. nth = 2n² + 2n + 13
17. nth = 3n² + n + 10
18. nth = 2n² + 2n + 14
19. nth = 3n² + 3n + 3
20. nth = 3n² + 2n + 4